Pequenas frases na mídia eletrônica brasileira : uma leitura discursiva - Bonácio, Daiany (2013)
Nowadays, it is common to see small phrases spread in the media which have been removed from their original context and they gained incalculable proportions of movement, being able to (re)create the most diverse discursive events. The current trend, reveals Krieg-Planque (2011), is the fragmentation of short discourses, due to the speed of the narrativization of the facts. The small phrase is a reality that newspapers, websites, social networks help to build when they publish the "phrases of the week", "the best phrases of the year", etc., and that makes us realize that the work of sobreasseveration and / or aforization is in full steam: never the spoken phrases and that they mark some event were so discussed and disseminated. According Maingueneau (2011b), the recent development of a media configuration that associate print media, television, internet, mobile, etc.., increased to an unprecedented level the detachment and the circulation of aforizations. For the author, some reach the state of the pandemic. Thus, for a short period of time, we see to circulate a sentence with a very high frequency in all media of the moment and that occopy a variety of statutes: newspaper titles, sentence at the bottom of the TV screen, etc.. In this thesis, we take as the object of study four small phrases that erupted on stable discursive fields and that, due to the rapid movement engendered, especially the Internet, became to appear in a various discursive fields. We attend a large file consisting of various discoursive genres (advertising, cartoon, humorous, journalistic comments on the net, etc.) and in which circulates notably four small phrases ―ai, se eu te pego‖, ―menos Luiza que está no Canadá‖, ―cala a boca, Galvão‖ and ―vada a bordo, cazzo‖. To account for this enterprise we adopt the Discourse Analysis of French orientation, especially the recents works of Alice Krieg-Planque (2011) and Dominique Maingueneau (2006a; 2006b; 2007; 2008; 2010; 2011a; 2011b; 2012a), reflections tha seek to understand accurately the production, circulation and transformation of small enunciates of political field. Our back question is to argue that, at presente due to the configuration media existing in our society, smalls phrases focus on various discursive fields.